Edge-based Linear Wave Equations on Quantum Trees with Dirichlet Vertex Conditions and Its Simulation - Burhan, M. J. I.; Soeharyadi, Y.; Budhi, W. S. (Methods of Functional Analysis and Topology, 2023)
We investigate the linear wave equations on the quantum trees S_N and P_2S_2 with Dirichlet vertex conditions at each leaf vertex. We first determine the edge-based Laplacian spectra on the quantum tree using quantitative analysis of the scattering matrix. This yields edge-based Laplacian spectral properties in the quantum trees S_N and P_2S_2, which we use to determine the general solution of the linear wave equation. Furthermore, we provide a solution to the wave equation with a Gaussian wave packet as an initial condition. We present an example of our numerical simulation. Досліджуються лінійні хвильові рівняння на квантових деревах S_N і P_2S_2 з вузловими умовами Діріхле на кожній вершині ребра. Спочатку визначаємо спектр лапласіана для кожного вузла на квантовому дереві за якісного аналізу матриці розсіювання. Це дає спектральні властивості лапласіана на кожному ребрі для квантових дерев S_N і P_2S_2, який далі використовується для визначення загального розв’язку лінійного хвильового рівняння. Крім того, розв’язано хвильове рівняння з хвильовим пакетом Гауса в якості початковій умови. Наведемо приклад чисельного моделювання.